Lowering voting age policy: factors influencing the level of acceptance in Malaysian society at Seremban / Nabilah Asyura Rahmat and Nur Najiha Hisham - Rahmat, Nabilah Asyura; Hisham, Nur Najiha
The research paper aims to discover the level of differences in thoughts and mindfulness of Malaysian society at Seremban and influencing factors on the issue of lowering voting age to 18 years old in Malaysia. There are some attributes that were applied in the research to identify the level of acceptance of the society such as the age of an individual, the maturity level of an individual, the youth’s political knowledge and the youth’s political participation. The problem statement of this research realizes the importance of the study as it is crucial to better understand the variables that determine the degree of Malaysian society's acceptance of the new voting age amendments. Based on the research, it was identified that the age of an individual is the main indicator that contributes to the level of acceptance of society in Seremban. This shows that the political involvement of youths could gain the trust and confidence of the people that the younger generations are brave, knowledgeable and democratic. The study suggested ways of increasing the youth’s awareness on the importance of having knowledge and understanding in politics.